Theological analysis of prophecy and its implication for the Church in Nigeria - Opalanwo, Samuel Omoniyi; Segun, Adediran Idowu; Ademola, J.O.; Adegbite , Deborah (Corpus Intellectual, 2024)
Prophecy is one of the ways God communicates with His people through his chosen vessels (prophets). It’s the voice that speaks with the authority of God for the benefit of humanity. Prophets prophesy the mind of God to the people and he stands in gap between God and man. As good as prophecy which should contribute to the development of the Church, abuse of it has bedeviled the Church and many lives, marriages, and destinies were ruined. The study therefore examines the effect of prophecy on the growth of the Church. The methodology used in this research is descriptive survey; questionnaires were administered to gather analyses. Findings revealed that prophecy brings about positive growth and development of The Church in Nigeria. It supports the improvement, expansion and unity through the directives that prophecy gives, and the Church in Nigeria at large hold firmly the prophecy and rely on the word of God, thus says the Lord, for glorious Future. It brings about edification, exhortation and comfort of the Church. The research recommended that authority of the Church should regulate the use of prophecy in the Church, train the prophets on how to use the gift of prophecies to prevent any form of abuse that may adversely affect the growth of the Church.